Problems of Transliteration of Fiqh Legal Terms (Library Research on The Book Al-Fiqh Al-Islami Wa Adillatuhu Using the Al-Munawwir Dictionary) - Daud, Izzat Muhammad; Ritonga, A. Husen; Yusuf, M. (Yayasan Sembilan Pemuda Indonesia, 2024)
This study investigates the difficulties encountered when translating fiqh terms from the Al-Munawwir dictionary to the “Islamic Fiqh wa Adillatuh” book. This study combines a literature review methodology with qualitative research techniques. The Al-Munawwir dictionary and legal jargon included in Sheikh Wahbah Az-Zuhaili’s book “Islamic Jurisprudence wa Adilatuh” are the sources of this information. The research’s findings indicate two categories of issues related to the translation of fiqh terminology in the book “Islamic Jurisprudence wa Adillatuh”: Linguistic Issues and Technical Issues. These issues were identified through data analysis conducted with the Al-Munawwir dictionary, followed by analysis and discussion in earlier chapters. This study further emphasizes how useful the Al-Munawwir lexicon is for translating terms related to fiqh. Among the Indonesian research and translation community that preserves their language, culture, and religion, this dictionary is highly regarded. Arabic and Indonesian dictionaries are used as reference materials, and words are defined from these sources.